Ultrasensitive microfluidic immunosensor with stir bar enrichment for point-of-care test of Staphylococcus aureus in foods triggered by DNAzyme-assisted click reaction. (1st June 2022) - Wang, Jiaqi; Tan, Lei; Bi, Wenchao; Shen, Haoyu; Li, Dengfeng; Yu, Zhenzhong; Gan, Ning
Graphic abstract: Highlights: An immunosensor based on a microfluidic chip was developed for the point-of-care test of S. aureus with a LOD of 3 CFU/mL. The prepared yolk antibody presented strong specificity, high stability, and low cost. A triple signal amplification strategy was used, including the enrichment of the stir bar, the high copper loading of polydopamine nanoparticles, and the DNAzyme-assisted click reaction. The microfluidic chip was served as a sensitive and portable signal detection platform. Abstract: This work demonstrated an ultrasensitive and simple microfluidic immunosensor for point-of-care test of Staphylococcus aureus ( S. aureus ) based on the stir bar enrichment and DNAzyme-assisted click reaction. Initially, S. aureus was enriched by the 4-mercaptophenylboronic acid-functionalized stir bar. The yolk antibody (immunoglobulin Y) and copper-labeled polydopamine nanoparticles were then specifically conjugated with the captured target. The Cu(II) was released under acidic conditions and effectively catalyzed the copper-catalyzed azide-alkyne cycloaddition (CuAAC) between the alkyne group-labeled DNAzyme and the streptavidin–biotin-azido with the assistance of DNAzyme. Finally, the DNAzyme-streptavidin complexes were detected by microfluidic chips to quantify S. aureus . Under optimum conditions, this immunosensor showed good detection performances toward S. aureus within 10 to 2.5 × 10 4 CFU/mL with a limit of detection of 3 CFU/mL. Moreover, the satisfying detection results of real samples of animal origin also implied that this immunosensor owned great potential in practical applications.